2010
DOI: 10.1243/09596518jsce950
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Specified H Loop Shaping Control for Balancing of Bicycle Robots: A Particle Swarm Optimization Approach

Abstract: In this paper, the particle swarm optimization (PSO) algorithm was used to design the structure-specified H ∞ loop shaping controllers for balancing of bicycle robots. The structure-specified H ∞ loop shaping controller design normally leads to a complex optimization problem. PSO is an efficient meta-heuristic search which is used to solve multi-objectives and non-convex optimizations. A model-based systematic procedure for designing the particle swarm optimization-based structure-specified H ∞ loop shaping co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 18 publications
1
12
0
1
Order By: Relevance
“…The controllers are of high order and achieve the same results as augmented plants through the application of a Riccati equation approach [15]. Several investigators have used nature-inspired search algorithms to design robust controllers [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The controllers are of high order and achieve the same results as augmented plants through the application of a Riccati equation approach [15]. Several investigators have used nature-inspired search algorithms to design robust controllers [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers who study self-balancing bicycles with mechanical regulators include Lee [7], Bui [8], Liu [9], Jin [10], Yin [11], Kim [12], etc. These researchers designed mechanical adjusting devices of moving or rotating for their bicycles.…”
Section: Introductionmentioning
confidence: 99%
“…Yavin 7 suggested that the symmetric bar or flywheel should not change the mass distribution of his bicycle when it is rotating, so it would be more convenient for maintaining bicycle's balance. Bui et al 8 were also concerned with the flywheel regulator in their design, and what is amazing is that their robot achieved a stable balance with zero moving velocity in a real experiment. Suebsomran 9 proposed upper and lower flywheels in their bicycle robot design.…”
Section: Introductionmentioning
confidence: 99%